Implementasi Kolaborasi Guru PAI Dengan Orang Tua Dalam Memotivasi Belajar Siswa Di Smp Swasta Pab 21 Pematang Johar - Iswani, Juni Tri; Sumanti, Solihah Titin; Azhar, Ihsan Satrya (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study was conducted to find out more about the collaboration process carried out by Islamic Religious Education teachers with parents in motivating student learning at SMP Swata PAB 21 Pematang Johar. This research method uses a qualitative method with a descriptive approach through data collection carried out by observation, interviews and documentation. The results obtained from this study indicate that; 1) The collaboration process between Islamic Religious Education teachers and parents in motivating student learning at SMP Swata PAB 21 Pematang Johar is carried out by holding direct meetings, making mutual agreements and making mutual understanding with the parents of students, then approaching students. 2) The form of collaboration between Islamic Religious Education teachers and parents in motivating student learning at SMP Swata PAB 21 Pematang Johar is carried out through direct communication, home learning assistance and conducting parenting incentives involving students' families, with an individual approach to students and the existence of parent organizations and Islamic Religious Education teachers in providing direct motivation. 3) Supporting and inhibiting factors in the collaboration of Islamic Religious Education teachers with parents in motivating student learning at SMP Swasta PAB 21 Pematang Johar, supporting collaboration of Islamic Religious Education teachers with parents is the involvement of parents in their children's learning at school, while the supporting factor in motivating student learning is the awareness of students about the importance of Islamic Religious Education learning.